O direito à comunicação no plenário da Assembléia Nacional Constituinte - Napolitano, Carlo José [UNESP] (Universidade Federal de Santa Maria, 2014)
This text is part of ongoing research that aims to verify the constitutional regulation of the communication rights, elaborated by constituent process on 87/88. For hypothesis, the research considers that was the intention of the constituent regulate the rights related to the communication. To fulfill to these objectives the research analyzes the legislative proposals and debates during the constituent process, related to the regulation of communication rights. In this text specifically will be presented the results of the research the parliamentary debates that had occurred in the plenary of the National Constituent Assembly. The partial results of the research point that the constituent intended to impose a social control to the communication rights, corroborating in this way this hypothesis of the research.

O presente trabalho trata-se de um relato parcial de pesquisa em andamento que pretende verificar a regulação do direito à comunicação, elaborado durante o processo constituinte de 87/88. Por hipótese, a pesquisa considera que a intenção constituinte era de regular os direitos relacionados à comunicação. Para cumprir esses objetivos a pesquisa analisa as propostas e os debates legislativos durante o processo constituinte, relativos à regulação do direito à comunicação. Neste trabalho especificamente serão apresentados os resultados da pesquisa nos debates parlamentares que ocorreram no plenário da Assembleia Nacional Constituinte. Os resultados parciais da pesquisa apontam que a constituinte pretendeu impor um controle social ao direito à comunicação, corroborando deste modo esta hipótese da pesquisa.
Keywords: Communication rights; Constituent process; Legal regulation; Direito à comunicação; Processo constituinte; Regulação jurídica